Preparation method of three-dimensional MXene / carbon quantum dot hybrid material for high-performance lithium ion battery negative electrode

By constructing a three-dimensional MXene/carbon quantum dot hybrid material with a three-dimensional honeycomb hollow microsphere structure, the problems of lithium-ion diffusion channel blockage and structural collapse caused by interlayer stacking of two-dimensional MXene nanosheets were solved, achieving efficient lithium-ion transport and long-term electrode stability.

CN121215731APending Publication Date: 2025-12-26HEFEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511401176.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-28
Publication Date
2025-12-26

AI Technical Summary

Technical Problem

Two-dimensional MXene nanosheets are prone to interlayer stacking during electrode fabrication, which leads to blockage of lithium-ion diffusion channels. Furthermore, structural collapse caused by volume expansion during charge-discharge cycles severely affects their cycle stability and electrochemical performance.

Method used

A three-dimensional MXene/carbon quantum dot hybrid material with a three-dimensional honeycomb hollow microsphere structure was constructed by electrostatic self-assembly of MXene nanosheets onto the surface of polylactic acid microspheres, followed by high-temperature heat treatment to generate carbon quantum dots, forming a hybrid material with a highly graphitized structure, which expands the interlayer spacing and enhances conductivity.

Benefits of technology

It significantly improves the electrochemical performance of lithium-ion battery anode materials, enhances lithium-ion transport efficiency, strengthens structural stability and electrode cycle life, and improves reversible capacity and long-term cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121215731A_ABST
    Figure CN121215731A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a three-dimensional MXene / carbon quantum dot hybrid material for a negative electrode of a high-performance lithium ion battery, which comprises the following steps: by taking cationic polylactic acid (CPLA) microspheres as a self-sacrifice template, uniformly coating the surface of CPLA with negatively charged MXene nanosheets through electrostatic self-assembly in deionized water to form a composite microsphere precursor; then vacuum freeze drying and high-temperature heat treatment are carried out, CPLA is decomposed, carbon quantum dots are induced to be generated in situ, the hybrid material composed of the three-dimensional MXene hollow microspheres and the carbon quantum dots is obtained, and the carbon quantum dots are of a highly-graphitized ordered structure and are stably attached to the surfaces and the interlayers of the hollow microspheres. When the material is used as a negative electrode of a lithium battery, the unique three-dimensional porous structure and surface characteristics of the material form a synergistic effect, so that the specific surface area is effectively increased, the charge transfer resistance is reduced, the stability of an ion transmission channel and an electrode structure is optimized, and the reversible capacity and cycle performance of the battery are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery anode materials, specifically relating to a method for preparing a three-dimensional MXene / carbon quantum dot hybrid material for high-performance lithium-ion battery anodes. Background Technology

[0002] Lithium-ion batteries (LIBs), as the current mainstream energy storage technology, have been deeply integrated into portable electronic devices, electric vehicles, and smart grids. Their performance improvement heavily relies on innovative breakthroughs in anode materials. Two-dimensional transition metal carbonitrides (MXenes), with their metal-like conductivity, abundant surface functional groups, and high theoretical capacity, have become important candidates for LIB anode materials, providing new solutions to problems such as insufficient capacity of traditional carbon-based anodes and poor conductivity of metal oxide anodes.

[0003] However, two-dimensional MXene nanosheets are prone to interlayer stacking during electrode fabrication, which leads to blockage of lithium-ion diffusion channels and significantly reduces ion transport efficiency. At the same time, the structural collapse of MXene due to volume expansion during charge-discharge cycles severely restricts its cycle stability, becoming a core bottleneck hindering its practical application.

[0004] To overcome this limitation, researchers turned their attention to the construction of three-dimensional (3D) MXene structures, building 3D-MXene frameworks using techniques such as cryogenic casting and electrostatic assembly. This design effectively expands the interlayer spacing of MXene, providing ample space for lithium-ion insertion / extraction while mitigating volume expansion through an interconnected network structure, and maintaining electrolyte wetting continuity, significantly improving the stacking and stability issues of 2D-MXene. However, 3D-MXene still suffers from incomplete elimination of interlayer stacking, resulting in narrow lithium-ion transport channels, low utilization of surface active sites, and poor conductivity and charge transfer efficiency, making it difficult to fully realize its electrochemical performance potential. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing a three-dimensional MXene / carbon quantum dot (3D-MXene / CQDs) hybrid material for high-performance lithium-ion battery anodes. By constructing two-dimensional MXene nanosheets into a three-dimensional honeycomb-like hollow microsphere structure and combining it with CQDs, a 3D-MXene / CQDs hybrid material is obtained. The CQDs exhibit a highly graphitized ordered structure and are stably attached to the surface and interlayer of the hollow microspheres. The introduction of CQDs provides a new direction for optimizing the performance of 3D-MXene. CQDs can serve as nano-spacer units to further expand the interlayer spacing of 3D-MXene, constructing lithium-ion transport channels; the hollow spheres increase the specific surface area to expose more active sites and improve structural stability; and the doping of CQDs enhances conductivity and reduces charge transfer resistance, thereby improving the high reversible capacity and long-term cycle stability of lithium-ion batteries.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a three-dimensional MXene / carbon quantum dot hybrid material for high-performance lithium-ion battery anodes involves first using positively charged cationic polylactic acid microspheres (CPLA) as a self-sacrificing template, and then uniformly coating negatively charged MXene nanosheets onto the CPLA surface via electrostatic self-assembly in deionized water to form a composite microsphere precursor. Next, vacuum freeze-drying and high-temperature heat treatment are performed to decompose the CPLA and induce in-situ generation of carbon quantum dots (CQDs), resulting in a hybrid hollow microsphere (3D-MXene / CQDs) material composed of three-dimensional MXene hollow microspheres and CQDs. Finally, this hybrid material is used as an active material to prepare a lithium-ion battery anode.

[0008] In the hybrid hollow microsphere (3D-MXene / CQDs) structure prepared by this invention, the CQDs exhibit a highly graphitized ordered structure and are attached in situ to the surface and interlayer of the MXene framework.

[0009] As a preferred technical solution of the present invention, the specific steps of the preparation method are as follows:

[0010] Step 1, Preparation of positively charged cationic polylactic acid microspheres (CPLA):

[0011] Polylactic acid (PLA) was dissolved in dichloromethane (DCM) to form an oil phase under stirring. Simultaneously, Tween 80 was dissolved in deionized water to form an aqueous phase, with the mass ratio of the aqueous phase to the oil phase controlled at 9:1 to 10:1. Under continuous stirring, the oil phase was added dropwise to the aqueous phase to form a stable O / W emulsion. Continuous stirring allowed the DCM to completely evaporate. After centrifugation, washing, and vacuum drying, white PLA microsphere powder was obtained. This powder was dispersed in an aqueous solution of polyethyleneimine (PEI) and reacted under stirring to aminate the surface of the PLA microspheres. After washing, positively charged cationic polylactic acid microspheres (CPLA) were obtained. Finally, these microspheres were redispersed in deionized water to obtain a CPLA dispersion.

[0012] Step 2, Preparation of MXene-coated CPLA composite nanospheres (CPLA@MXene):

[0013] The MXene dispersion and CPLA dispersion were mixed, stirred, and then freeze-dried under vacuum to obtain CPLA@MXene composite nanosphere powder.

[0014] Step 3, Preparation of three-dimensional MXene / carbon quantum dot hybrid hollow microspheres (3D-MXene / CQDs):

[0015] CPLA@MXene powder was subjected to high-temperature heat treatment under a nitrogen atmosphere to remove the CPLA template, resulting in 3D-MXene / CQDs hybrid hollow microspheres.

[0016] Step 4, Preparation of the lithium-ion battery negative electrode:

[0017] 3D-MXene / CQDs hybrid hollow microspheres were used as the active material, mixed with Super P carbon black and polyvinylidene fluoride (PVDF), and ball-milled using N-methylpyrrolidone (NMP) as the solvent to prepare an electrode slurry. This slurry was then coated onto copper foil, vacuum dried, and cut into electrode sheets. The loading of the 3D-MXene / CQDs active material in the electrode sheets was 0.27–0.36 mg / cm³. 2 .

[0018] As a further preferred technical solution of the present invention, in step 1, the mass-to-volume ratio of PLA to DCM is 0.5g / 50mL~1.5g / 50mL, and the mass-to-volume ratio of Tween 80 to water is 1.5g / 50mL~5g / 50mL; the oil phase and the aqueous phase are simultaneously stirred at 25 °C for 2 h, and then the oil phase is added dropwise to the aqueous phase at a rate of 0.03~0.05 mL / s to generate a stable oil-in-water (O / W) emulsion; the emulsion is then magnetically stirred at 25 °C for 24 h to ensure complete evaporation of DCM, and then centrifuged, and washed alternately with deionized water and ethanol until no foam residue remains, and finally vacuum dried at 60 °C to obtain white PLA microsphere powder.

[0019] As a further preferred technical solution of the present invention, in step 1, 1~3 g of PLA microsphere powder is dispersed in 70~100 mL of 5wt% polyethyleneimine (PEI) aqueous solution and reacted for 24 h under magnetic stirring; washed by centrifugation with deionized water to obtain positively charged cationic polylactic acid microspheres (CPLA) with a diameter of 400~1000 nm; an appropriate amount of deionized water is added and ultrasonically dispersed for 10~20 min to prepare a CPLA dispersion with a concentration of 20~30 mg / mL.

[0020] As a further preferred technical solution of the present invention, in step 2, the concentration of the MXene dispersion is 3~5 mg / mL, the mass ratio of CPLA to MXene is 3:1~10:1, the MXene dispersion and the CPLA dispersion are stirred at room temperature for 3~4 h at a stirring speed of 500~2000 rpm; then frozen at -60~-20 ℃ for 10~20 h, and dried for 80~90 h to obtain CPLA@MXene powder with a diameter of 600~1200 nm.

[0021] As a further preferred technical solution of the present invention, in step 3, the CPLA@MXene powder is heated to 380~450 ℃ at a rate of 8~10 ℃ / min and kept at this temperature for 2~3 h under a nitrogen atmosphere to obtain 3D-MXene / CQDs hybrid hollow microspheres.

[0022] As a further preferred technical solution of the present invention, in step 4, 3D-MXene / CQDs are mixed with Super P carbon black and polyvinylidene fluoride (PVDF) at a mass ratio of 7:2:1, and N-methylpyrrolidone (NMP) is used as a solvent. The mixture is ball-milled for 3-4 h to prepare an electrode slurry, which is then coated onto a copper foil. After vacuum drying at 80 °C for 6-8 h, the slurry is cut into electrode sheets and assembled into a CR2032 battery.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0024] This invention constructs 3D-MXene / CQDs hybrid hollow microspheres with a three-dimensional honeycomb porous structure from two-dimensional MXene nanosheets, significantly improving the electrochemical performance of lithium-ion battery anode materials. In this structure, CQDs with a highly graphitized ordered structure serve as nano-spacer units, effectively expanding the MXene interlayer spacing. Combined with the three-dimensional porous network, they alleviate the ion channel blockage problem caused by the stacking of two-dimensional nanosheets, promoting rapid cross-layer transport of lithium ions. Simultaneously, the 3D-MXene framework provides excellent mechanical buffering for the electrode during charge and discharge, suppressing volume changes. The CQDs further enhance the overall structural stability, thereby significantly improving the cycle life and capacity retention of the electrode. Furthermore, the three-dimensional porous structure significantly increases the specific surface area of ​​the material, exposing more active sites, which helps improve the reversible capacity and long-term cycle stability of the electrode. Attached Figure Description

[0025] Figure 1 This is a scanning electron microscope image of the 3D-MXene / CQDs hybrid hollow microspheres prepared in Example 2.

[0026] Figure 2 This is a transmission electron microscope (TEM) image of the 3D-MXene / CQDs hybrid hollow microspheres prepared in Example 2.

[0027] Figure 3 This is a high-resolution transmission electron microscope (TEM) lattice fingerprint of CQDs obtained after purifying the 3D-MXene / CQDs hybrid hollow microspheres prepared in Example 2.

[0028] Figure 4 The graph shows the 1000-cycle performance of a battery assembled using 3D-MXene / CQDs hybrid hollow microspheres prepared in Example 2 as the active material. Detailed Implementation

[0029] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings.

[0030] Example 1

[0031] 1. 2.7 g of Tween 80 was dissolved in 90 mL of deionized water to form an aqueous phase, while 0.3 g of PLA was dissolved in 10 mL of dichloromethane (DCM) to prepare an oil phase, ensuring a water-to-oil ratio of 9:1. The mixture was then stirred simultaneously at 25 °C for 2 h. The oil phase was then added dropwise to the aqueous phase at a rate of 0.04 mL / s to generate a stable oil-in-water (O / W) emulsion. This emulsion was subsequently magnetically stirred at 25 °C for 24 h to ensure complete evaporation of the dichloromethane. The resulting PLA microspheres were centrifuged and alternately washed with deionized water and ethanol until no foam residue remained. Finally, they were vacuum dried at 60 °C to obtain a white PLA microsphere powder.

[0032] 2. Disperse 2.5 g PLA microspheres in 100 mL of 5 wt% PEI aqueous solution and react for 24 h under magnetic stirring. After the reaction, wash with deionized water 6 times to obtain PEI-functionalized cationic PLA microspheres. Then add 20 mL of deionized water and ultrasonically disperse for 20 min to obtain CPLA dispersion with a concentration of 26 mg / mL and a diameter of about 700 nm for the CPLA microspheres.

[0033] 3. Weigh 0.5 g each of aluminum titanium carbon and lithium fluoride powder and add them sequentially to a 50 mL centrifuge tube. Add 2.5 mL of deionized water and 7.5 mL of concentrated hydrochloric acid sequentially. Seal the centrifuge tube with plastic wrap and make a hole. Stir magnetically at 400 rpm for 48 h. Centrifuge and wash until the pH reaches 7. Take an appropriate amount of deionized water to dissolve the precipitate, sonicate for 45 min, centrifuge at 4000 rpm for 5 min, and collect the supernatant to obtain the MXene dispersion with a concentration of 3.8 mg / mL.

[0034] 4. Mix 45.61 mL of MXene dispersion with 20 mL of CPLA dispersion using magnetic stirring. The mass ratio of CPLA to MXene is 3:1. Stir at 700 rpm for 4 h at room temperature. Freeze CPLA@MXene at -60 ℃ for 20 h and freeze-dry under vacuum for 90 h. Remove the CPLA template by high-temperature heat treatment, heating to 420 ℃ at a rate of 9 ℃ / min and holding at that temperature for 2.5 h under a nitrogen atmosphere.

[0035] In Example 1, the 3D-MXene / CQDs microspheres, in addition to completely covering the surface of the CPLA microspheres, have excess nanosheets that continue to stack on the outside of the coating layer, forming multi-layered thick shells or adhering to each other, with a pore size of approximately 780 nm. This structure increases ion diffusion paths and masks some active sites, resulting in impaired battery rate performance and capacity retention.

[0036] Example 2

[0037] 1. Dissolve 3 g of Tween 80 in 100 mL of deionized water to form an aqueous phase, and simultaneously dissolve 0.3 g of PLA in 10 mL of dichloromethane (DCM) to prepare an oil phase, ensuring a water-to-oil ratio of 10:1. The mixture was then stirred simultaneously at 25 °C for 2 h. The oil phase was then added dropwise to the aqueous phase at a rate of 0.05 mL / s to generate a stable oil-in-water (O / W) emulsion. This emulsion was subsequently magnetically stirred at 25 °C for 24 h to ensure complete evaporation of the dichloromethane. The resulting PLA microspheres were centrifuged and alternately washed with deionized water and ethanol until no foam residue remained. Finally, they were vacuum dried at 60 °C to obtain a white PLA microsphere powder.

[0038] 2. Disperse 2 g PLA microspheres in 100 mL of 5 wt% PEI aqueous solution and react for 24 h under magnetic stirring. After the reaction, wash with deionized water 6 times to obtain PEI-functionalized cationic PLA microspheres. Then add 20 mL of deionized water and ultrasonically disperse for 20 min to obtain CPLA dispersion with a concentration of 25 mg / mL and a diameter of about 640 nm for the CPLA microspheres.

[0039] 3. The preparation method is the same as in Example 1, and an MXene dispersion with a concentration of 4 mg / mL is obtained.

[0040] 4. Mix 37.5 mL of MXene dispersion with 30 mL of CPLA dispersion using magnetic stirring. The mass ratio of CPLA to MXene is 5:1. Stir at 600 rpm for 3 h at room temperature. Freeze CPLA@MXene at -60 ℃ for 20 h and freeze-dry under vacuum for 90 h. Remove the CPLA template by high-temperature heat treatment, heating to 410 ℃ at a rate of 10 ℃ / min and holding at that temperature for 2 h under a nitrogen atmosphere.

[0041] 5. 0.16 g of 3D-MXene / CQDs was used as the active material and mixed with Super P and PVDF in a mass ratio of 7:2:1. NMP was used as the solvent and the mixture was ball-milled for 3 h to prepare an electrode slurry. The slurry was coated onto copper foil, vacuum dried at 80 °C for 8 h, cut into electrode sheets, and assembled into CR2032 type batteries.

[0042] 6. As a comparison, 0.16 g of MXene (same as step 3 of Example 1, centrifuged and washed without dispersion, directly frozen at -60°C for 20 h and dried for 90 h) was used as the active material and mixed with Super P and PVDF at a mass ratio of 7:2:1. Using NMP as solvent, the mixture was ball-milled for 3 h to prepare an electrode slurry, which was coated onto copper foil, vacuum dried at 80°C for 8 h, cut into electrode sheets, and assembled into CR2032 type batteries.

[0043] like Figure 1 As shown, the 3D-MXene / CQDs hybrid hollow microspheres prepared in Example 2 of the present invention exhibit a three-dimensional honeycomb porous structure, mainly composed of relatively regular hollow spherical MXene, with a pore size of approximately 750 nm.

[0044] like Figure 2 As shown, in the 3D-MXene / CQDs hybrid hollow microspheres prepared in Example 2 of the present invention, CQDs are attached to the inner and outer surfaces and interlayer of the MXene hollow microspheres.

[0045] like Figure 3 As shown, after purification, the 3D-MXene / CQDs hybrid hollow microspheres prepared in Example 2 exhibited a highly graphitized ordered structure. High-resolution transmission electron microscopy analysis revealed the presence of a hexagonal lattice similar to graphene within them; the measured d 100 The interplanar spacing is 0.212 ± 0.002 nm, indicating that the carbon atoms inside the CQDs have a nanoscale ordered arrangement.

[0046] like Figure 4 As shown, at a high rate of 5C, the initial specific capacity of the 3D-MXene / CQDs electrode is 259.34 mAh g⁻¹. -1 It remained stable at 218.38 mAh g after 1000 cycles. -1 The capacity retention rate can reach 84.2%, indicating that it has good long-term cycle stability and rate performance.

[0047] Example 3

[0048] In comparison, step 1 of Example 2 was modified as follows: 2.85 g of Tween 80 was dissolved in 95 mL of deionized water to form an aqueous phase, while 0.3 g of PLA was dissolved in 10 mL of dichloromethane (DCM) to prepare an oil phase, ensuring a water-to-oil ratio of 9.5:1. All other components remained unchanged, resulting in PLA powder.

[0049] 2. 2.3 g PLA microspheres were dispersed in 100 mL of 5 wt% PEI aqueous solution and reacted under magnetic stirring for 24 h. After the reaction, the microspheres were washed 6 times with deionized water to obtain PEI-functionalized cationic PLA microspheres. Then, 20 mL of deionized water was added and ultrasonically dispersed for 20 min to obtain a CPLA dispersion with a concentration of 25 mg / mL and a diameter of about 680 nm for the CPLA microspheres.

[0050] 3. The preparation method is the same as in Example 1, and an MXene dispersion with a concentration of 4.2 mg / mL is obtained.

[0051] 4. Mix 17.86 mL of MXene dispersion with 30 mL of CPLA dispersion using magnetic stirring. The mass ratio of CPLA to MXene is 10:1. Stir at 670 rpm for 200 min at room temperature. Freeze CPLA@MXene at -60 ℃ for 20 h and freeze-dry under vacuum for 90 h. Remove the CPLA template by high-temperature heat treatment, heating to 450 ℃ at a rate of 8 ℃ / min and holding at that temperature for 3 h under a nitrogen atmosphere.

[0052] The 3D-MXene / CQDs obtained in Example 3 consist of a large number of irregular spherical MXenes and a small number of relatively intact hollow spherical MXenes, with a pore size of approximately 720 nm. Irregular spherical MXenes are prone to structural collapse during cycling, resulting in longer and more irregular electron transport paths, which affects the electron conduction efficiency in the electrodes and reduces the initial specific capacity and cycle stability of the battery.

[0053] Analysis of the above comparative experiments shows that the ratio of CPLA to MXene directly affects the microstructure of the final 3D-MXene / CQDs, and thus affects their electrochemical performance.

Claims

1. A method for preparing a three-dimensional MXene / carbon quantum dot hybrid material for a high-performance lithium-ion battery anode, characterized in that, First, positively charged cationic polylactic acid microspheres (CPLA) were used as self-sacrificing templates. Negatively charged MXene nanosheets were uniformly coated onto the CPLA surface through electrostatic self-assembly in deionized water to form a composite microsphere precursor. Then, CPLA was decomposed and carbon quantum dots (CQDs) were induced to form in situ through vacuum freeze-drying and high-temperature heat treatment, resulting in a hybrid hollow microsphere material (3D-MXene / CQDs) composed of three-dimensional MXene hollow microspheres and CQDs. Finally, this hybrid material was used as an active material to prepare a lithium-ion battery anode.

2. The method as described in claim 1, characterized in that, In the prepared hybrid hollow microsphere (3D-MXene / CQDs) structure, the CQDs exhibit a highly graphitized ordered structure and are attached in situ to the surface and interlayer of the MXene framework.

3. The preparation method according to claim 1 or 2, characterized in that, The steps are as follows: Step 1, Preparation of positively charged cationic polylactic acid microspheres (CPLA): Polylactic acid (PLA) was dissolved in dichloromethane (DCM) to form an oil phase under stirring. Simultaneously, Tween 80 was dissolved in deionized water to form an aqueous phase, with the mass ratio of the aqueous phase to the oil phase controlled at 9:1 to 10:

1. Under continuous stirring, the oil phase was added dropwise to the aqueous phase to form a stable oil-in-water (O / W) emulsion. Continuous stirring allowed the DCM to completely evaporate. After centrifugation, washing, and vacuum drying, white PLA microsphere powder was obtained. This powder was dispersed in an aqueous solution of polyethyleneimine (PEI) and reacted under stirring to aminate the surface of the PLA microspheres. After washing, positively charged cationic polylactic acid microspheres (CPLA) were obtained. Finally, these microspheres were redispersed in deionized water to obtain a CPLA dispersion. Step 2, Preparation of MXene-coated CPLA composite nanospheres (CPLA@MXene): The MXene dispersion and CPLA dispersion were mixed, stirred, and then freeze-dried under vacuum to obtain CPLA@MXene composite nanosphere powder. Step 3, Preparation of three-dimensional MXene / carbon quantum dot hybrid hollow microspheres (3D-MXene / CQDs): CPLA@MXene powder was subjected to high-temperature heat treatment under a nitrogen atmosphere to remove the CPLA template, resulting in 3D-MXene / CQDs hybrid hollow microspheres. Step 4, Preparation of the lithium-ion battery negative electrode: 3D-MXene / CQDs hybrid hollow microspheres were used as the active material, mixed with Super P carbon black and polyvinylidene fluoride (PVDF), and ball-milled using N-methylpyrrolidone (NMP) as the solvent to prepare an electrode slurry. This slurry was then coated onto copper foil, vacuum dried, and cut into electrode sheets. The loading of the 3D-MXene / CQDs active material in the electrode sheets was 0.27–0.36 mg / cm³. 2 .

4. The preparation method according to claim 3, characterized in that, In step 1, the mass-to-volume ratio of PLA to DCM was 0.5 g / 50 mL to 1.5 g / 50 mL, and the mass-to-volume ratio of Tween80 to water was 1.5 g / 50 mL to 5 g / 50 mL. The oil phase and the aqueous phase were simultaneously stirred at 25 °C for 2 h. Then, the oil phase was added dropwise to the aqueous phase at a rate of 0.03 to 0.05 mL / s to generate a stable oil-in-water (O / W) emulsion. The emulsion was then magnetically stirred at 25 °C for 24 h to ensure complete evaporation of DCM. After centrifugation, the emulsion was washed alternately with deionized water and ethanol until no foam residue remained. Finally, it was vacuum dried at 60 °C to obtain white PLA microsphere powder.

5. The preparation method according to claim 4, characterized in that, In step 1, 1-3 g of PLA microsphere powder is dispersed in 70-100 mL of 5 wt% polyethyleneimine (PEI) aqueous solution and reacted under magnetic stirring for 24 h; the microspheres are washed by centrifugation with deionized water to obtain positively charged cationic polylactic acid microspheres (CPLA) with a diameter of 400-1000 nm; an appropriate amount of deionized water is added and ultrasonically dispersed for 10-20 min to prepare a CPLA dispersion with a concentration of 20-30 mg / mL.

6. The preparation method according to claim 5, characterized in that, In step 2, the concentration of the MXene dispersion is 3-5 mg / mL, the mass ratio of CPLA to MXene is 3:1-10:1, and the MXene dispersion and CPLA dispersion are stirred at room temperature for 3-4 h at a stirring speed of 500-2000 rpm. Then, they are frozen at -60 to -20 °C for 10-20 h and dried for 80-90 h to obtain CPLA@MXene powder with a diameter of 600-1200 nm.

7. The preparation method according to claim 6, characterized in that, In step 3, the CPLA@MXene powder is heated to 380-450 ℃ at a rate of 8-10 ℃ / min and kept at this temperature for 2-3 h under a nitrogen atmosphere to obtain 3D-MXene / CQDs hybrid hollow microspheres.

8. The preparation method according to claim 7, characterized in that, In step 4, 3D-MXene / CQDs are mixed with Super P carbon black and polyvinylidene fluoride (PVDF) at a mass ratio of 7:2:

1. N-methylpyrrolidone (NMP) is used as a solvent. The mixture is ball-milled for 3-4 h to prepare an electrode slurry, which is then coated onto copper foil. After vacuum drying at 80 °C for 6-8 h, the slurry is cut into electrode sheets and assembled into a CR2032 battery.